Increased exercise tolerance using daytime mouthpiece ventilation for patients with diaphragm paralysis. Issue 3 (September 2017) - Koopman, Maud; Vanfleteren, Lowie E.G.W.; Steijns, Sander; Wouters, Emiel F.M.; Sprooten, Roy
Diaphragmatic paralysis can be either unilateral or bilateral. It is a rare condition and can have several causes [1]. As the diaphragm is the most important muscle of inspiration, diaphragmatic paralysis commonly complicates ventilation. Mouthpiece ventilation can improve exercise tolerance in patients with unilateral or bilateral diaphragm paralysis http://ow.ly/X2Pd30dCT7n